Real-World Outcomes of CDK4/6 Inhibitors Treatment in Metastatic Breast Cancer in Romania - Andreea-Iuliana Miron; Alexandra-Valentina Anghel; Andrei-Alexandru Barnonschi; Ruxandra Mitre; Horia-Dan Liscu; Estera Găinariu; Raluca Pătru; Simona Coniac (Diagnostics, 2023)
The introduction in clinical practice of selective cyclin-dependent kinase (CDK) 4/6 inhibitors improves the outcome of patients with hormone receptor (HR)-positive human epidermal growth factor receptor 2 (HER2)-negative metastatic breast cancer (mBC). In Romania, the three available CDK 4/6 inhibitors (Palbociclib, Ribociclib and Ademaciclib) have been approved by the National Agency for Medicines (ANM) in 2019, 2020 and 2021. We conducted a retrospective study from 2019 to 2022 on 107 patients with metastatic breast cancer HR+ that have been treated with CDK 4/6 inhibitors in addition to hormone therapy in the Oncology Department of Colțea Clinical Hospital in Bucharest. The purpose of this study is to calculate the median progression-free survival (PFS) and to compare it with the median PFS from other randomized clinical trials. A key difference from other studies is that our study evaluated both patients with non-visceral mBC and patients with visceral mBC, as these two groups often have different outcomes. A total of 79.4% were postmenopausal patients and 20.6% were premenopausal; 42.1% had different stages at the beginning of disease and 57.9% presented newly metastatic disease. Median PFS was 17 months, unlike randomized clinical trials which reported a median PFS of 25.3 months. The combination of CDK 4/6 inhibitors with endocrine therapy is the golden standard treatment in HR-positive, HER2-negative metastatic breast cancer, bringing a prolongation of survival for these patients. Our results show no major differences compared to randomized clinical trials, despite the smaller patient group. In order to have a picture of the efficacy of the treatment as close as possible to the real-world data, we believe that it would be very useful to have a collaboration between several oncology departments in different institutions to carry out a multi-center study on large groups of patients.